The dagger Quick - Eames, Brian (Simon & Schuster Books for Young Readers, 2013)
Twelve-year-old Christopher "Kitto" Wheale, a clubfooted boy seemingly doomed to follow in the boring footsteps of his father as a cooper in seventeenth-century England, finds himself on a dangerous seafaring adventure with his newly discovered uncle, the infamous pirate William Quick.